2006
DOI: 10.1111/j.1469-7580.2006.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive changes of retinal astrocytes and Müller glial cells in kainate‐induced neuroexcitotoxicity

Abstract: The aim of this study was to investigate reactive changes of astrocytes and Müller glial cells in rats subjected to kainate treatment, which leads to neuronal degeneration in the ganglion cell layer and the inner border of the inner nuclear layer as confirmed by labelling with Fluoro-Jade B, a marker for degenerating neurons and fibres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 40 publications
2
81
0
3
Order By: Relevance
“…These reports suggested that the decrease in the number of cells observed in the GCL after intravitreal glutamate injections might have resulted from a loss of amacrine cells and from a lack of trophic support for RGCs. KA induces activation of retinal astrocytes and Müller cells, which reflects a metabolic change of the cells in response to degenerative changes of their neighboring neurons, which may give evidence of repair process in KA-induced damage [5]. Previous studies have shown that Pax6 mRNA was expressed during development of the mouse retina and in the adult mouse retina [21] and was upregulated during retinal regeneration [13].…”
Section: Discussionmentioning
confidence: 99%
“…These reports suggested that the decrease in the number of cells observed in the GCL after intravitreal glutamate injections might have resulted from a loss of amacrine cells and from a lack of trophic support for RGCs. KA induces activation of retinal astrocytes and Müller cells, which reflects a metabolic change of the cells in response to degenerative changes of their neighboring neurons, which may give evidence of repair process in KA-induced damage [5]. Previous studies have shown that Pax6 mRNA was expressed during development of the mouse retina and in the adult mouse retina [21] and was upregulated during retinal regeneration [13].…”
Section: Discussionmentioning
confidence: 99%
“…This serum was also specific for GFAP on immunoblots in extracts from the mouse spinal cord 24) and rat retina 25) .…”
Section: Glial Fibrillary Acidic Protein (Gfap)mentioning
confidence: 95%
“…As a general measure of glial reactivity, we examined immunolabeling intensity of the astrocyte marker GFAP and the Müller glia marker glutamine synthetase. An increase in the expression of these markers is associated with increased reactivity or activation of astrocytes and Müller glia in response to a variety of stressors in retina [37][38][39][40][41][42][43][44]. Since we evaluated overall labeling intensity, increases in GFAP or glutamine synthetase levels can be attributed to either increased expression on a per cell basis, which accompanies hypertrophy, or an increase in density.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that uptake and anterograde transport of CTB by RGCs is an early indicator of RGC decline [34][35][36]. Similarly, expression of GFAP by astrocytes and glutamine synthetase by Müller cells is altered in response to retinal damage, including glaucoma [37][38][39][40][41][42][43][44]. For our analysis in whole mount retina, we sampled 60x fields in the area between mid-central and mid-peripheral retina.…”
Section: Stressor-dependent Changes In Gp130 Are Accompanied By Altermentioning
confidence: 99%